An evaluation study of different methods for the production of β‐D‐glucan from yeast biomass. Issue 1 (20th July 2015) - Varelas, Vassileios; Liouni, Maria; Calokerinos, Antony C.; Nerantzis, Elias T.
Abstract : β ‐Glucan is a proven beneficial and valuable molecule for human and animal health systems. It can be incorporated as an ingredient in various functional foods and beverages. β ‐Glucan has been isolated from various biological sources, fungi, mushrooms, algae, plants, and bacteria. The yeast cell wall comprises a suitable target for the extraction and purification of β ‐glucan. Although there are various extraction techniques, significant differences are observed as the technique used affects the final yield and purity, molecular weight, biological activity, solubility, quality, and other biological and functional properties of the extracted β ‐glucan. The aim of this review is the evaluation of different extraction methods for the production of β ‐glucan from yeast biomass. Furthermore, the use of industrial spent yeast waste from breweries and the wine industry for biotechnological β ‐glucan production and the concept of green wineries and breweries are discussed. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : β ‐Glucan is a valuable molecule molecule for the human and animal health system. The yeast cell wall, particularly of baker's and brewer's yeast Saccharomyces cerevisiae, is an important source of β‐D ‐glucans. For yeast β ‐glucan, many extraction methods have been proposed. Yeast cells can be exploited for β ‐glucan production. Brewery and winery spent yeast biomass can comprise an alternative source for β ‐glucan production.